Mexico and the united states during the presidential crisis in nicaragua, january-november 1926 - Meza Bazán, Mario (2023)
The crisis of the presidential succession in Nicaragua between 1926 and 1927 was an opportunity for the revolutionary regime of Mexico led by Plutarco Elías Calles to recover the influence of the country in Central America. This action particularly involved a political, diplomatic and even military confrontation with the United States of America, a country with which it had to compete for the recognition of the constitutional legitimacy of the vice-presidency of the liberal Juan B. Sacasa, overthrown by the coup d’état of General Emiliano Chamorro. We analyze the political motivations of the Calles government and the diplomatic and military capacity of his government to intervene in this conflict of an international nature but which ventilated, at the same time, the tensions that the Mexican country had against the economic and political interests of the United States.